Impact of a multidisciplinary approach on antibiotic consumption, cost and microbial resistance in a Czech hospital - Mach, Rene; Vlcek, Jiri; Prusova, Miroslava; Batka, Petr; Rysavy, Vladan; Kubena, Ales (Pharmacy world & science, 2007)
OBJECTIVE: The study objective was to evaluate the impact of a restrictive antibiotic policy, efficacy of inpatient therapeutic and prophylactic antibiotic regimens and susceptibility patterns of infecting bacteria in 2000-2004. SETTING: A 500-bed general hospital in the Czech Republic. METHOD: A retrospective computerized survey of antibiotic prescribing practices over a five-year period 2000-2004, using medical records and laboratory data from the hospital information system (HIS). MAIN OUTCOME MEASURE: Consumption of antibiotics expressed in defined daily doses (DDDs) and Euros per 1,000 bed days. Resistance to antibiotics, average length of hospital stay, rate of inpatients treated with antibiotics, number of nosocomial infections per 1,000 bed days, median length of hospital stay and total mortality. RESULTS: Due to a restrictive antibiotic policy implemented in 2002, the use of several antibiotics in 2003 was significantly reduced but the consumption of several other antibiotics rose in 2003. In comparison with 2001 the cost of antibiotic agents (in Euro per 1,000 inpatient days) fell significantly by 31% in 2003 Euro 969.07 vs. Euro 671.34). The hospital saved about Euro 29,288 after the first year of implementation of the new antibiotic policy. The use of restricted antibiotics increased by 8%; however, the expenditure decreased by 26%. For non-restricted antibiotics, the use and expenditure decreased by 71% and 41%, respectively. Consequently, a net reduction of 55% Euro 804.36 vs. Euro 359.36) was achieved. CONCLUSION: The intervention was effective in reducing the use and cost of antibiotics. The HIS is a helpful tool for observing and evaluating the impacts of the measures taken and can be used for assessment of pharmacotherapy outcomes.
Keywords: Drug Utilization; směrnice pro lékařskou praxi jako téma; Practice Guidelines as Topic; Anti-Bacterial Agents; bakteriální léková rezistence; Drug Resistance, Bacterial; Cost Savings; nemocnice všeobecné; Retrospective Studies; Bacterial Infections; Length of Stay; délka pobytu; Česká republika; bakteriální infekce; nemocnice - lůžková kapacita 500 a více; Cross Infection; Microbial Sensitivity Tests; Czech Republic; Cost Control; kontrola nákladů; Hospital Bed Capacity, 500 and over; úspory nákladů; retrospektivní studie; Humans; nemocniční informační systémy; antibakteriální látky; infekce spojené se zdravotní péčí; Hospitals, General; spotřeba léčiv; Hospital Information Systems; mikrobiální testy citlivosti; lidé